2013
DOI: 10.1016/j.neuroscience.2013.07.052
|View full text |Cite
|
Sign up to set email alerts
|

Acute and delayed protective effects of pharmacologically induced hypothermia in an intracerebral hemorrhage stroke model of mice

Abstract: Hemorrhagic stroke, including intracerebral hemorrhage (ICH), is a devastating subtype of stroke; yet, effective clinical treatment is very limited. Accumulating evidence has shown that mild to moderate hypothermia is a promising intervention for ischemic stroke and ICH. Current physical cooling methods, however, are less efficient and often impractical for acute ICH patients. The present investigation tested pharmacologically induced hypothermia (PIH) using the second generation neurotensin receptor (NTR) ago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 75 publications
(105 reference statements)
1
46
0
Order By: Relevance
“…Safer and more effective methods for producing TH are needed that are compatible with conscious subjects to make TH a viable treatment option for a broader patient population. Indeed, there has been renewed interest in a variety of pharmacological methods of promoting hypothermia without the need for sedation (19,45).…”
Section: Discussionmentioning
confidence: 99%
“…Safer and more effective methods for producing TH are needed that are compatible with conscious subjects to make TH a viable treatment option for a broader patient population. Indeed, there has been renewed interest in a variety of pharmacological methods of promoting hypothermia without the need for sedation (19,45).…”
Section: Discussionmentioning
confidence: 99%
“…They show high affinity for human NTR1 and induce regulated hypothermia in a dose-dependent manner (Hadden et al, 2005; Orwig et al, 2009). Our group has demonstrated that acute and delayed administrations of HPI-201 and HPI-363 show marked protective effects against brain injury after ischemic and hemorrhagic strokes as well as traumatic brain injury (TBI) in adult and neonatal rodent models (Choi et al, 2012; Lee et al, 2014; Lee et al, 2016b; Wei et al, 2013). NRT1 agonists additionally show antinociceptive and antipsychotic actions (Guillemette et al, 2012; Mechanic et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We did not assess initial severity, which would be interesting given that the effects of TH would likely diminish with smaller doses of collagenase (e.g., less or no hematoma expansion after smaller bleeds). Finally, our results likely apply to other cooling methods, such as intentional druginduced TH (Wei et al, 2013) or unintended cooling (e.g., drug side effect).…”
Section: Discussionmentioning
confidence: 80%